2015
DOI: 10.1002/bse.1905
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Effects of Sustainability‐Oriented Incentive Systems

Abstract: Companies increasingly extend their existing incentive systems by integrating several sustainable performance indicators. Although these ‘sustainability‐oriented’ incentive systems clearly highlight which business objectives should be attained, little is known about the effects that these incentive systems have on employee behavior. Based on signaling theory, social identity theory and a person–organization fit (PO‐fit) perspective, we assume positive relations between sustainability‐oriented incentive systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 106 publications
(175 reference statements)
3
32
0
Order By: Relevance
“…Our findings also add to prior work on CSP signalling (Corazza et al ., ; Huber and Hirsch, ; Jones et al ., ; Zerbini, in press) by shedding light on how the valence and content of indirect CSP signals affect the magnitude of shareholders' responses to CSP‐related information. We found that negative indirect CSP signals caused larger changes in firm value than positive indirect CSP signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings also add to prior work on CSP signalling (Corazza et al ., ; Huber and Hirsch, ; Jones et al ., ; Zerbini, in press) by shedding light on how the valence and content of indirect CSP signals affect the magnitude of shareholders' responses to CSP‐related information. We found that negative indirect CSP signals caused larger changes in firm value than positive indirect CSP signals.…”
Section: Discussionmentioning
confidence: 99%
“…Given the existence of information asymmetries about the level of a firm's CSP, signalling theory provides a useful framework to explore the influence of CSP on firm performance (for a discussion, see Connelly et al ., ; Zerbini, in press), and has thus often been used in the CSR literature (Corazza et al ., ; Huber and Hirsch, ; Jones et al ., ). This theory is concerned with understanding how two parties resolve information asymmetries about what one party (e.g.…”
Section: Conceptual Background and Hypotheses Developmentmentioning
confidence: 99%
“…Sustainability implicates that enterprises have the responsibility to not only acquire financial profits and maintain economic growth, but also consider external stakeholders’ economic interests and their environmental and social influences (Dahlsrud, ). Through communications, enterprises can gain the support of sustainability management within the organization, obtain societal legitimation, empower employees to respond to societal demands (Huber and Hirsch, ; Jansson et al , ; Signitzer and Prexl, ), actively stimulate consumers to rethink their demands and further promote sustainable consumption to meet public needs of society (Signitzer and Prexl, ).…”
Section: Introductionmentioning
confidence: 99%
“…Against the twenty‐first century tumult of discontinuous and exponential change, the issue of sustainability has soared to prominence within corporate and academic domains (Huber & Hirsch, ). The basic notion of sustainability has existed within the human lexicon for over three centuries (Fischler, ); however, substantive progress has been elusive (Howes et al, ; Steffen et al, ) and further obfuscated by escalating corporate rhetoric (Ihlen, ).…”
Section: Introductionmentioning
confidence: 99%
“…They conclude that narrow strategies are not viable, and both institutional and internal forces need to come into play, in particular positive attitudes on behalf of senior management. Huber and Hirsch () studied sustainability‐oriented incentive systems in relation to employee behaviour, specifically attraction, motivation and cooperation. Their research found that employee attitude towards sustainability moderates the link between incentive systems and behaviour, which suggests strategic human resource management implications to ensure strong person‐organization fit.…”
Section: Introductionmentioning
confidence: 99%